Issues of personal self-realization in the concept of education by J. Krishnamurti - Pendyurina Lyudmila (SHS Web of Conferences, 2019)
The article discusses the problems of individual development and self-development, put forward in the teachings of the Indian thinker J. Krishnamurti, explores the specifics of the humanistic approach in the modern cultural educational space. The author analyzes the content of the cultural-like and cultural-creation paradigm of J. Krishnamurti’s education and upbringing, reveals its main ideas and provisions, traces the ways of forming psychological and mental attitudes that have internal constant value. The article gives an analysis of the projective pedagogical and educational decisions of J. Krishnamurti, allowing you to change the idea of education as an information-cognitive process and remove the narrowly focused scientific and utilitarian principles of its construction.